Taxonomic refinement of Bacillus thuringiensis - Shiekh Suliman, Nagham; Talaei-Hassanloui, Reza; Abachi, Hamid; Zarei, Sadegh; Osdaghi, Ebrahim (Frontiers in Microbiology, 2025)
Bacillus thuringiensis is the most important biological control agent against various agricultural pests. The bacterium taxonomically belongs to the Bacillus cereus group, which also contains human pathogenic species, e.g., Bacillus anthracis. Thus, precise identification and taxonomic delineation of candidate strains for agricultural usage is of high importance in terms of both public health and biosecurity. By October 2023, whole genome sequences (WGS) of 885 bacterial strains were labeled as B. thuringiensis in the NCBI GenBank database. This study investigates the taxonomic authenticity of those strains using DNA similarity indexes, i.e., average nucleotide identity (ANI) and digital DNA–DNA hybridization (dDDH). All strains were compared with the type strain of B. thuringiensis ATCC 10972T. WGS-based phylotaxonomic investigations showed that out of 885 strains 803 strains authentically belonged to B. thuringiensis while 82 strains were mislabeled as B. thuringiensis having dDDH and ANI values less than the acceptable threshold of 70 and 95% respectively, for prokaryotic species definition in comparison with the B. thuringiensis type strain. Among these 82 mislabeled strains, 39 strains need to be reclassified within the B. cereus group in the species B. anthracis (33 strains), Bacillus toyonensis (five strains), and Bacillus mycoides (one strain). Furthermore, four strains were identified as Bacillus tropicus while one strain belonged to each of the species Bacillus licheniformis, Bacillus paranthracis, and Bacillus weidmannii. The remaining 36 strains did not match with any known Bacillus species nor the species of other bacterial genera, thus they could be assigned to hypothetical new species. Results of the present study, on the one hand, pave the way of comprehensive taxonomic refinements within B. thuringiensis species. On the other hand, highlight the role of taxonomic investigations in targeting authentic B. thuringiensis strains for biological control purposes.